’Setomonogatari’: Ceramic Practice as an Archaeology of the Contemporary Past - McHugh, Chris (Journal of Contemporary Archaeology, 2018)
I will argue that my creative ceramic practice has much in common with archaeological approaches to the contemporary past in that it takes the form of a “creative materialising intervention”, focusing on marginal or otherwise overlooked aspects of person-object interaction. This will be illustrated by reference to recent artworks made in Seto, Japan, a traditional centre of pottery production. By reanimating old moulds and repurposing discarded sherds, my work explores the site’s changing materiality through time and is itself a proactive contribution to the archaeological record, capturing an enduring glimpse of the past and present of this ceramics community.